Coaxiality evaluation based on double material condition. (July 2019) - Tang, Zhemin; Huang, Meifa; Sun, Yonghou; Zhong, Yanru; Qin, Yuchu; Huang, Jing
Highlights: Coaxiality-DM error could be verified with a virtual gauge. A virtual gauge consists of two coaxial cylindrical virtual boundaries. The checking by virtual gauge is described as a constrained optimization problem. The model could be solved by current optimization techniques such as SQP. The proposed method produces higher accuracy than the current T-Map method. Abstract: To ensure the assemblability of a workpiece, Coaxiality-DM can be applied to two coaxiality cylinders. According to this specification, the relative orientation and location between an actual datum feature and the derived datum axis are variable. Thus, the Coaxiality-DM tolerance is mainly verified by real gauges, which is costly for small batch production. To develop a proper tool for that production, a evaluation model for Coaxiality-DM tolerance was investigated in this paper. According to the International Organization for Standardization (ISO), the geometry of the real gauge was analyzed, and a virtual gauge model was established. Based on the model, an evaluation method was proposed. Furthermore, an example of a stepped shaft was provided to illustrate the applicability of the proposed method. Finally, a comparative experiment was carried out, and the results revealed that the proposed model could produce more accurate results than the existing mathematical methods.